Effect of protein synthesis inhibitors on leukocytic pyrogen-induced in vitro hypothalamic prostaglandin production. - Bernheim, H. A. (Yale Journal of Biology and Medicine, 1985)
In order to study the antipyretic effect of inhibitors of protein synthesis, hypothalamic tissue was incubated in vitro under controlled conditions and the amount of prostaglandin E2 (PGE2) measured in the supernatant medium. Rabbit anterior hypothalamic tissue was incubated with purified human leukocytic pyrogen (LP) and after 60 minutes the supernatant fluid was assayed for PGE2 by radioimmunoassay. Control tissue incubated with Eagle's medium (MEM) released elevated levels of PGE2; however, the addition of polymyxin B (PmxB), a cationic antibiotic which blocks the activities of bacterial endotoxins, significantly reduced PGE2. In addition, endotoxin added to MEM induced from the brain tissue PGE2 production which could be reduced by the addition of PmxB. Thus, commercial culture media such as MEM may contain sufficient amounts of endotoxin to stimulate brain PGE2 production in vitro. Purified human LP incubated with hypothalamic tissue in the presence of PmxB induced PGE2 production in a dose-dependent fashion. This release could be reduced (p less than 0.001) by the presence of either cycloheximide or puromycin during incubation with LP. The addition of these inhibitors to unstimulated hypothalamic tissue incubations did not reduce background levels of PGE2. It is concluded that the antipyretic effect of protein synthesis inhibitors results in a specific decrease in LP-induced levels of PGE2.